Antibactertial property and toxcity study of medicinal plant Tinospora Crispa l. / Altammar Khadijah Ahmed Y. - Altammar Khadijah, Ahmed Y. (2010)
Tinospora crispa is a medically important herb used for centuries in traditional medicine for the treatment of various ailments. The aim of this study was to investigate the safety of the aqueous and alcoholic extract of Tinospora crispa by determining its toxicological effects after acute administration in rats, and to investigate the antibacterial activity of both extracts. Disc diffusion and broth dilution methods were carried out in determining the antibacterial effects of the plant extract on the pure cultures of clinical isolates of 8 MRSA and S. aureus ATCC strain. The disc-diffusion method of the ethanolic extracts showed inhibition zone on the tested organisms. The minimum inhibitory concentration (MIC) of the ethanolic extracts on the tested organisms after 48 hours was 25 mg/ml while that of aqueous extract has no effect on majority of the test organisms. Acute toxicity study with a higher dose of 4 g/kg ethanolic extract and 2 g/kg aqueous extracts did not manifest any toxicological signs in rats. However, aqueous extract showed mortality at 4 g/kg. No significant changes of biochemical parameters (liver and renal functions) were observed between control groups and surviving rats. In conclusion, it was demonstrated that ethanolic extract of T. crispa is a promising anti-MRSA agent, and the value of LD50 was estimated as greater than administrated dose (4 g/kg).